Green Production of a High-Value Branched-Chain Diester: Optimization Based on Operating Conditions and Economic and Sustainability Criteria - Claudia Montiel; Silvia Gimeno-Martos; Salvadora Ortega-Requena; Mar Serrano-Arnaldos; Fuensanta Máximo; Josefa Bastida (Applied Sciences, 2023)
Branched-chain esters (BCEs) have found a large number of applications in cosmetics. Among them, neopentyl glycol dilaurate (NPGDL) stands out as an emollient, emulsifier, and skin-conditioning agent. This work presents the synthesis of NPGDL in a solvent-free medium using the two most common immobilized lipases: Novozym® 40086 (Rml) and Novozym® 435 (CalB). Results proved that the former biocatalyst has lower activity and certain temperature deactivation, although conversions ≥ 90% were obtained at 60 °C and 7.5% of catalyst. On the other hand, optimal reaction conditions for Novozym® 435 are 3.75% w/w of the immobilized derivative at 80 °C. Under optimal conditions, the process productivities were 0.105 and 0.169 kg NPGDL/L h, respectively. In order to select the best conditions for NPGDL production, studies on the reuse of the derivative and cost estimation have been performed. Economic study shows that biocatalytic processes can be competitive when lipases are reused for five cycles, yielding biocatalyst productivities of 56 and 122 kg NPGDL/kg biocatalyst using Novozym® 40086 and Novozym® 435, respectively. The final choice will be based on both economic and sustainability criteria. Green metric values using both biocatalysts are similar but the product obtained using Novozym® 40086 is 20% cheaper, making this alternative the best option.